Effectiveness of Synchronized Noninvasive Ventilation to Prevent Intubation in Preterm Infants - Cristina Ramos-Navarro; Manuel Sanchez-Luna; Ester Sanz-López; Elena Maderuelo-Rodriguez; Elena Zamora-Flores (Thieme Medical Publishers, Inc., 2016)
Abstract Background Noninvasive ventilation is being increasingly used on preterm infants to reduce ventilator lung injury and bronchopulmonary dysplasia. The aim of this study was to evaluate the effectiveness of synchronized nasal intermittent positive pressure ventilation (SNIPPV) to prevent intubation in premature infants. Methods Prospective observational study of SNIPPV use on preterm infants of less than 32 weeks' gestation. All patients were managed using a prospective protocol intended to reduce invasive mechanical ventilation (iMV) use. Previous respiratory status, as well as respiratory outcomes and possible secondary side effects were analyzed. Results SNIPPV was used on 78 patients: electively to support extubation on 25 ventilator-dependent patients and as a rescue therapy after nasal continuous positive airway pressure failure on 53 patients. For 92% of patients in the elective group and 66% in the rescue group, iMV was avoided over the following 72 hours. No adverse effects were detected, and all patients were in a stable condition even if intubation was eventually needed. Conclusions The application of SNIPPV in place of or to remove mechanical ventilation avoids intubation in 74.4% of preterm infants with respiratory failure. No adverse effects were detected.